Age and health related inheritance taxation - Marie-Louise Leroux; Pierre Pestieau (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2021)
This paper studies the design of an optimal non linear inheritance taxation when individuals differ in wage as well as in their risks of both mortality and old-age dependance. We assume that the government cannot distinguish between bequests motives, that is whether bequests result from precautionary reasons or from pure joy of giving reasons. Instead, we assume that it only observes whether bequests are made early in life or late in life, and in the latter case, whether the donor is autonomous or not. The main result is that, under asymmetric information, in addition to labour income taxation, early bequests of the low-productivity agent should be distorted downward, that is, they should be taxed so as to relax incentive constraints.
Keywords: H21; H23; I14; 330; Bequest taxation; Long term care; Utilitarianism; Old-age dependency; Nonlinear taxation